Exploring pneumonia risk factors in Vietnamese infants: a survey of new mothers. Issue 1 (10th August 2017) - Phuong, Nguyen TK; Hoang, Tran T; Foster, Kirsty; Roberts, Christine L; Marais, Ben J
Abstract : Objective: To understand the prevalence of pneumonia risk factors and perceived barriers to risk factor reduction among Vietnamese infants. Methods: We conducted a cross-sectional survey of mothers in the postnatal wards of Da Nang Hospital for Women and Children in central Vietnam from 10 February 2017 to 24 February 2017. Results: Of 286 mothers surveyed, 259 (91%) initiated breast feeding and 207 (72%) intended to continue exclusive breast feeding for 6 months. No mother smoked cigarettes, but 42% of fathers did. Mothers' decision not to smoke was motivated by concerns for their own health and that of their baby. Households rarely used wood or coal for cooking (6%). Mothers indicated near universal (99%) uptake of the National Expanded Program of Immunization vaccinations. Few (64; 22%) mothers knew about the pneumococcal conjugate vaccine; 56/64 (88%) indicated that they would purchase it for their infants. Family members rarely influenced mothers' decisions about breast feeding or vaccination, except in two instances where fathers were concerned about vaccine-related adverse effects. Conclusion: Modifiable pneumonia risk factors were uncommon among newborn babies in central Vietnam, apart from paternal cigarette smoke exposure. Successful local implementation of the WHO Essential Newborn Care package as well as high levels of maternal education and decision autonomy was observed.